Characterization of Actinobacillus pleuropneumoniae field strains antigenically related to the 3-6-8-15 group from diseased pigs in Japan and Argentina = Caracterización de cepas de Actinobacillus pleuropneumoniae antigénicamente relacionados al grupo 3-6-8-15 obtenidos de cerdos infectados naturalmente en Japón y Argentina - To, Ho (2018)
The objectives of this study were to determine the serovar of a collection of Actinobacillus pleuropneumoniae strains within the 3-6-8-15 cross-reacting group and to analyze their phenotypic and genetic properties. Based on the serological tests, forty-seven field strains of Actinobacillus pleuropneumoniae isolated from lungs with pleuropneumonia lesions in Japan and Argentina were found to be serovars belonging to the 3-6-8-15 cross-reacting group. By using a capsule loci-based PCR, twenty-nine (96.7%) and one (3.3%) from Japan were identified as serovars 15 and 8, respectively, whereas seventeen (100%) from Argentina were identified as serovar 8. The findings suggested that serovars 8 and 15 were prevalent within the 3-6-8-15 cross-reacting group, in Argentina and Japan, respectively. Phenotypic analyses revealed that the protein patterns observed on SDS–PAGE and the lipopolysaccharide antigen detected by immunoblotting of the reference and field strains of serovars 8 and 15 were similar to each other. Genetic (16S rDNA, apxIIA, apxIIIA, cps, cpx genes, apx and omlA patterns) analyses revealed that the apxIIA and apxIIIA genes of the field strains of serovars 8 and 15 were similar to those of the reference strains of serovars 3, 4, 6, 8 and 15. The results obtained in the present study may be useful for the development of more effective vaccines against disease caused by A. pleuropneumoniae by including the homologous antigens to the most prevalent serovars in specific geographical areas.